Hubungan Kemampuan Bercerita Guru Dengan Kecerdasan Linguistik Anak Kelompok B Di TK Al Islam 14 Mipitan Mojosongo Jebres Surakarta Tahun Ajaran 2015/2016 - Rahayu, Herning, Drs. Ilham Sunaryo, M.Pd AUD, WILI ASTUTI, S.Pd., M.Hum (2016)
This study aimed to identify the reliationship storytelling ability of teachers to linguistik intelegence and the research find that there is a reliationship storytelling ability of teacher to the children linguistic intelegence in group B in TK Al-Islam 14 Mipitan Mojosongo Jebres Surakarta year 2015/2016. This research uses descriptive quantitative research. This research was conducted in TK AL-ISLAM 14 Mipitan Mojosongo Jebres Surakarta for group B in the school year 2015/2016. The research sample as many as 30 children of group B in TK AL-ISLAM 14 Mipitan Mojosongo Jebres Surakarta 30 children in group B. Sampling using simple random sampling. Collecting data using the method of observation and questionnaire method. Hypothesis testing using the product moment correlation. Based on the analysis that there is a reliationship story-telling ablility of teachers to use props to linguistic intelligence of children in group B at TK AL-ISLAM 14 Mipitan Mojosongo Jebres Surakarta year 2015/2016. This is evidenced by the result amounted to 0,742 with a significantly by 0,000<0,01 (p = 0,000; p<0,01) which means there is a significant relationship between the ability to tell the teacher uses props to linguistic intelegence of children in group B at TK AL-ISLAM 14 Mipitan Mojosongo Jebres Surakarta year 2015/2016. Keywords teacher's ability to tell a story, linguistic intelegence